When 3D echocardiography truly makes the difference: a case report of mitral annular ring dehiscence. - Sartorio, Daniele; Borrello, Bruno; Tuttolomondo, Domenico; De Filippo, Massimo; Gaibazzi, Nicola (Acta Biomedica Atenei Parmensis, 2021)
Real time 3D echocardiography has an established incremental diagnostic value over 2D imaging, especially during transesophageal evaluation of native and prosthetic heart valves. A 66 years old male patient, with an history of previous cardiac surgery for mitral annuloplasty and recurrent fever, came to the attention of our echo lab with an indication for transesophageal echocardiography after previous inconclusive transthoracic echocardiograms. Real time 3D echocardiography and 3D color doppler imaging resulted of outmost importance to clarify the presence of annular ring dehiscence, previously not well defined from 2D echocardiography imaging.